An Analysis of the semantic relationships among tsukau, riyousuru, and shiyousuru in Japanese news media - Huzain, Nurimam Alfian; Imelda, Imelda; Taqdir, Taqdir (Japanese Research on Linguistics, Literature, and Culture, 2025)
This research is conducted to find out the similarities and differences of the three verbs.This research discusses the semantic relationship between the verbs tsukau, riyousuru, shiyousuru in Japanese news media where the three verbs have similar meanings or the same meaning which is "using" when translated into Indonesian. In addition, the method of substitution in the sentence is used to find out the relationship of the three verbs. The data used in this research is obtained from Japanese news media that are always up to date, namely NHK Japan, Yomiuri Shinbun, and Asahi Shinbun, which always present Japanese news to international media.The method of data collection, data analysis, and descriptive analysis. For further analysis, a descriptive qualitative method was used. The three verbs have the same meaning, which is to use or utilize objects or goods for a particular purpose. The similarity of meaning can substitute each other in sentences and can be classified into synonymous meaning relations. However, the difference in meaning between tsukau, riyousuru, and shiyousuru makes the three verbs unable to substitute each other in sentences.